Genotypic variation in Na, K and their ratio in 45 commercial cultivars of Indian tropical onion: A pressing need to reduce hypertension among the population - Singh, Hira; Lombardo, Mauro; Goyal, Abhishek; Kumar, Amrender; Khar, Anil (Frontiers in Nutrition, 2023)
According to the WHO, high sodium and low potassium are implicated in the pathogenesis of hypertension (HTN), which is the basic and foremost cause of stroke, myocardial infarction and death. A population-based approach and precision nutrition are needed to prevent and cure HTN. The prevalence of HTN has been rising globally and has been attributed to the aging of the population and sedentary lifestyles, such as a lack of exercise, obesity, unhealthy diets and food containing higher table salt, resulting in much higher sodium intakes than the recommended level. Majority of junk food, processed food and packaged foods have higher sodium contents. To counter the effects of diet on HTN, identification of high potassium/sodium ratio plant-based food is needed. Among fruits and vegetables, onion could be the ideal option since it contains high potassium content. Keeping this in mind, we evaluated forty-five commercially short day Indian onion cultivars for potassium and sodium content and their ratio. Wide variation among the genotypes for potassium, sodium and potassium/sodium ratios were observed. The K content was recorded as significantly highest in the yellow-coloured bulb variety ‘Arka Pitamber’ (9160.07 ± 96.74) followed by Pusa Sona (7933.20 ± 292.81). On the other hand, minimal K was assessed in the white-coloured bulb variety ‘Agrifound White’ (490.27 ± 17.01) followed by Udaipur Local (732.93 ± 93.42). Twelve cultivars exhibited >7000 mg K content, while nine cultivars recorded <1500 mg. On the contrary, Na was recorded as significantly highest in the dark-red-coloured bulbs and the lowest in white bulbs. More than thirty-five-fold difference was observed between the highest and lowest K/Na ratio in the bulbs of tested cultivars. Cluster analysis revealed three major groups comprising of 23, 13 and 9 genotypes. This information could form the base for public health, food and onion researchers to design suitable cultivars to prevent HTN as a population-wide approach. The next century is going to be food-based for the amelioration of human diseases in a sustainable way without any after-effects on the human body. Research into developing varieties for this purpose is needed after thorough investigation at both physiological and molecular levels.